2021
DOI: 10.47405/mjssh.v6i1.617
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Herbal Medicine Usage in Diabetes Management: A Qualitative Study amongst Type 2 Diabetes Mellitus Patients and Health Care Providers in Negeri Sembilan, Malaysia

Abstract: The use of herbal medicine (HM) and its products has significantly increased in the past decade. Type 2 Diabetes mellitus patients (T2DM) are always rendering herbal medicine as an alternative to the current option of treatment to manage their disease. This article is aimed to explore the extent of communication process of patients who disclose their HM usage to healthcare providers (HCPs) and HCP’s experiences in managing these patients. Purposive sampling method was applied in this qualitative study, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In a recent study about the usage of TM and AM in healthcare facilities, it was discovered that patients lacked adequate engagement and were afraid of AMPs (Mokhesi & Modjadji 2022 ). Furthermore, bad interactions between patients and AMPs may lead to the patients feeling pitiful, frightened, and demoralised at the same time (Amirudin et al 2021 ). Hence, AMPs need to enhance their communication with patients as their negative responses are the main drivers of the fear the patients have for them (Hajj et al 2020 ; Amirudin et al 2021 ).To improve communication between AMPs and patients about TM use, AMPs must consider the likelihood of their patients using TM and be objective in their interactions with these patients during a consultation (James et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study about the usage of TM and AM in healthcare facilities, it was discovered that patients lacked adequate engagement and were afraid of AMPs (Mokhesi & Modjadji 2022 ). Furthermore, bad interactions between patients and AMPs may lead to the patients feeling pitiful, frightened, and demoralised at the same time (Amirudin et al 2021 ). Hence, AMPs need to enhance their communication with patients as their negative responses are the main drivers of the fear the patients have for them (Hajj et al 2020 ; Amirudin et al 2021 ).To improve communication between AMPs and patients about TM use, AMPs must consider the likelihood of their patients using TM and be objective in their interactions with these patients during a consultation (James et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, bad interactions between patients and AMPs may lead to the patients feeling pitiful, frightened, and demoralised at the same time (Amirudin et al 2021). Hence, AMPs need to enhance their communication with patients as their negative responses are the main drivers of the fear the patients have for them (Hajj et al 2020;Amirudin et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they should create a conducive environment, AMPs should respect their patients' beliefs about TM and be aware of the implications of not disclosing its use during consultations [11]. Previous studies found that AMPs can facilitate this dialogue by asking direct questions which can elicit numerous reasons for non-disclosure [12,13]. Undoubtedly, discussing their TM usage with the AMPs is crucial for the overall well-being of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they should create a conducive environment, AMPs should respect their patients’ beliefs about TM use and be aware of the implications of not disclosing its use during consultations [ 15 ]. Previous studies found that AMPs can facilitate this dialogue by asking direct questions which can elicit numerous reasons for non-disclosure [ 12 , 16 ]. Undoubtedly, discussing their TM usage with the AMPs is crucial for the overall well-being of these patients.…”
Section: Introductionmentioning
confidence: 99%